Monotonicity, Convexity, and Inequalities Involving the Agard Distortion Function - Yu-Ming Chu; Miao-Kun Wang; Yue-Ping Jiang; Song-Liang Qiu (Abstract and Applied Analysis)
We present some monotonicity, convexity, and inequalities for the Agard distortion function ηK(t) and improve some well-known results.